Consumer Behavior In Islamic Economic Perspective - Erni Murniati; Fikri Zuhri (Proceeding International Seminar of Islamic Studies, 2019)
The large variety and variety of choices to meet the needs of life will greatly benefit consumers. Consumers are more free to choose according to their needs as desired. Consumers can choose from the cheapest price to the most expensive price. Depending on the budget (budget) and consumer desires. However, consumers often react to changing their minds at the last minute when deciding to make a purchase. This is where, consumer behavior occupies an important position in decision making. Behavior is an individual activity to evaluate, obtain, use, or manage goods and services. Many factors affect consumer behavior. These factors are cultural, social, personal and psychological factors of the buyer. In addition to these things, there is another factor that is very important in consumer decision making, namely motivation. Motivation itself as a giver and driver that creates a person's enthusiasm so that they want to work together, work effectively, and integrated with all efforts to achieve satisfaction. In Islam there is a clear distinction, namely halal and haram. In other words, in an economic activity it is prohibited to mix up the halal and haram. This is part of the consumption limit in Muslim consumer behavior.